2013
DOI: 10.1590/s0103-84782013000800002
|View full text |Cite
|
Sign up to set email alerts
|

Goiabeiras Paluma, Pedro Sato e Cortibel 6 propagadas por miniestaquia e miniestaquia seriada

Abstract: A técnica da miniestaquia seriada consiste na coleta de brotações de miniestacas previamente enraizadas e tem proporcionado efeito positivo sobre o revigoramento de alguns clones de eucalipto. O objetivo deste trabalho foi avaliar a sobrevivência e o enraizamento de miniestacas seriadas de goiabeiras Paluma, Pedro Sato e Cortibel 6. O experimento foi conduzido em delineamento de blocos casualizados (DBC), com quatro repetições, sendo cada parcela constituída por três miniestacas. Sessenta e dois dias após o es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…It was verified that the seedlings grown on the Bioplant ® substrate obtained a larger stem diameter, where a mean diameter of 1.08 mm was verified. According to Freitas et al (2013) in a study of the production of seedlings grown on substrate with humic acid, it was verified that the Bioplant ® substrate demonstrated efficiency in the development of guava plants. These authors also observed that the sand substrate, although being well used in the seed germination process, does not present colloidal or nutrient properties, and it is necessary to add other organic sources to obtain superior results in both germination and plant development.…”
Section: Resultsmentioning
confidence: 99%
“…It was verified that the seedlings grown on the Bioplant ® substrate obtained a larger stem diameter, where a mean diameter of 1.08 mm was verified. According to Freitas et al (2013) in a study of the production of seedlings grown on substrate with humic acid, it was verified that the Bioplant ® substrate demonstrated efficiency in the development of guava plants. These authors also observed that the sand substrate, although being well used in the seed germination process, does not present colloidal or nutrient properties, and it is necessary to add other organic sources to obtain superior results in both germination and plant development.…”
Section: Resultsmentioning
confidence: 99%
“…According to Freitas et al (2013) The degree of success of the propagation will depend on the interaction between these factors, the possibility of manipulation and the knowledge of each specie needs. For , the environmental variations and the characteristics of each season of the year are factors that can cause variation in the production of buds in the mini-stumps and rooting of the minicuttings.…”
Section: Season/year Of the Collectionsmentioning
confidence: 99%
“…The use of clonal mini-gardens for the production of mini-cuttings is being used in several crops, such as guava (Freitas et al, 2013), 'pitangueira' (Peña et al, 2015), blueberries (Affonso et al, 2015) and forestry species such as Cedrela fissilis (Xavier et al, 2003), Toona ciliata (Souza et al, 2014) and Paulownia fortunei (Stuepp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As miniestacas são obtidas de minitouceiras, e estudos recentes têm apontado a miniestaquia como técnica promissora para produção de mudas de goiabeiras, possibilitando ganhos no enraizamento de cultivares menos propensas a emitir raízes adventícias, como é o caso da 'Cortibel 6', pertencente a um grupo de variedades cultivadas no Espírito Santo (FREITAS et al, 2013).…”
Section: Introductionunclassified